Costly Adjustment under Rational Expectations: A Generalization - Pesaran, M. Hashem (The Review of Economics and Statistics, 1991)
This note provides a generalization of the standard adjustment cost-rational expectations model due to Sargent (1978), which, in addition to the cost of changing the level of the decision variable, also allows for the cost of altering the "speed" with which decisions are changed. It establishes the existence of a unique stable solution for this more general model, derives an explicit solution for the underlying decision problem, and provides a necessary order condition for identification of the structural parameters. The note also contains an application of the model to the determination of employment in the U.K. coal industry over the 1956-83 period. Copyright 1991 by MIT Press.